I'jaz Al-Qiraat Al-Quraniyyah : an analysis on Ijaz Al-Bayani In Tafsir Mafatih Al-Ghayb - Muhammad Hafiz Jamil (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
The research in this dissertation focuses on the I'jaz al-Bayani, which is based on the interpretation of Qira'at verses (variants or multiple Qura'nic recitations) in Tafsir Mafatih Al-Ghayb by Fakhruddin al-Razi. In the context of understanding the relationship between Qira'at and I'jaz al-Bayani, al-I'jaz enticed readers and researchers in the elaboration of the multiple differences in Qira'at through his acclaimed Qur'anic exegesis Mafatih Al-Ghayb (The Keys of the Unknown). Taking into account the variations in Qira'at recitations, this research aims to examine the elements of I'jaz al-Bayani in Qira'at verses in the Qur'an. In this study, the researcher released the entire Qira'at recitations found in Surah al-Baqarah in Tafsir Mafatih al-Ghayb, or better known as Tafsir al-Razi. The methodology in this study involved data collection and analysis through the qualitative method, which is the method that puts emphasis on the formation of theory inductively. The result shows that the interpretation by al-Razi in interpreting Qira'at verses gave remarkably high aesthetic values. Therefore, the values of the Qira'at interpretation, especially on I'jaz al-Bayani, opens up a broad discussion of all kinds of issues in the best way and leaves a deep impression. On top of that, this analysis provides valuable insights into the existence of I'jaz in those Qira'at verses, and it clearly proves the greatness and miracle of the Qur'an – inimitable, comprehensive and everlasting in its truths.